Conflict reporting in the High North. Signs of peace journalism in Norwegian media representations of Russians? Case study. The Elektron incident - Lundberg, Lene (UiT Norges arktiske universitet, 2017)
The case study of this thesis is the incident with the Russian trawler Elektron in 2005. The trawler was fishing illegally in the Barents Sea, and escaped from Norwegian authorities with two Norwegian fisheries inspectors on board. The event stirred up the military, governments and the news media. The aim of this analysis is to look at how Russian actors are framed in the Norwegian media. The concept of Peace Journalism has provided the theoretical framework. By doing a media analysis through the lenses of Peace Journalism, as well as interviews with persons of both nationalities, I have examined representations of Russians and the relationship between the two states. The analysis shows that most news articles frame Russians in a neutral way. This indicates that the media aims for balanced reporting. However, most articles do not fulfill the criteria of Peace Journalism. The sources, editors and news contributors are almost exclusively male elites. There is a lack of investigation into structural causes of the problem with illegal fishing, and almost no evidence of a win-win orientation or creative suggestions to conflict solution. In addition, the interviews show that there is mutual mistrust and conflicting interests between Norwegians and Russians. This suggests that the states have a negative peace rather than a positive peace. But the interviewees also stress the importance of the long lasting, and successful, joint management of the fisheries in the Barents Sea.